Empirical Formula for Assessment Concrete Compressive Strength by Using Ultrasonic Pulse Velocity - Shakir Al-Aasm, Hameed (International Journal of Engineering and Technology, 2018)
Statistical practical program was carried out to establish a fairly accurate empirical formula between compressive strength of concrete and ultrasonic pulse velocity. The work has a strong empirical base, but it is firmly governed by theory. In concrete, the compressive strength of concrete is related to the type, proportion and physical properties of aggregate but it is well known to be intensely affected by the properties of the cement paste, which relate, mainly, to the w/c ratio. The other variables such as age and density of concrete, salt content in fine aggregate and curing method have a relatively little effect on compressive strength of concrete. Therefore, the program involves field testing of reinforced concrete members that their w/c ratio and cube uniaxial compressive strength are known. The results were used as input data in statistical program (SPSS) to develop an empirical formula between the compressive strength of concrete and ultrasonic pulse velocity. The proposed formula was confirmed by the results of previous experiments. Although the relationship between the compressive strength of concrete and ultrasonic pulse velocity physically indirect, the statistical program revealed that the pulse velocity test could be used with acceptable error in evaluating the compressive strength of concrete.Â Â